"Suburbanas, Irreverentes e Mana-moças": uma pesquisa sociológica sobre a prostituição feminina de rua em um bairro da elite moçambicana, na cidade de Maputo - Muchanga, José Luís Magaço (2022)
This research explored the phenomenon of female street prostitution in Maputo City. Problematizing the current framework of sociological productions referring to the matter of street prostitution in Mozambique, the objective of this work was to understand the social dynamics that circumscribe the occurrence and reproduction of the referred phenomenon, in a neighborhood of the Mozambican elite (Sommerschield), in a context of stigma relegate to the activity. Based on a qualitative research methodology, and the adoption of field research and post-colonial theories, the main results of this work pointed to the fact that female street prostitution occurs in the Sommerschield neighborhood thanks to direct or indirect consent given to street prostitutes, by residents and other important stakeholders in the neighborhood. In fact, the research sought to broaden the reflection on the subject in question here, in the Mozambican urban context, aiming at greater knowledge management about the ways of life, interfaces and conflicts arising from the activity, in a social context marked by relationships of social inequalities, but also by intense negotiations, creativity and resistence.